2017
DOI: 10.18178/joaat.4.3.274-279
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance in Silica Production Technologies from Agricultural Waste Stream–Review

Abstract: Substantial applications of silica materials in industrial products have caused development of silica extraction methodologies out of various waste products. Rice husk /straw and wheat husk/straw (agricultural waste) are one of the agricultural wastes which have a huge content of silicate materials. This review shows that silica production techniques by using thermal and chemical methods, and also provide directions to efficient, new, rapid microwave assisted method for silica extraction from agricultural wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…Thermal methods involve the utilization of furnace muffles, fixed bed furnace, fluidized bed reactor, and other thermal methods that consist of inclined step-grate furnace, cyclone furnace, and rotary kiln. The thermal technology does have a number of disadvantages such as required more time for reaction, hot spot formation, the absence of free-flowing air for full carbon oxidation, and many others [26].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…Thermal methods involve the utilization of furnace muffles, fixed bed furnace, fluidized bed reactor, and other thermal methods that consist of inclined step-grate furnace, cyclone furnace, and rotary kiln. The thermal technology does have a number of disadvantages such as required more time for reaction, hot spot formation, the absence of free-flowing air for full carbon oxidation, and many others [26].…”
Section: Thermal Methodsmentioning
confidence: 99%
“…110,111 Approaches for the extraction of biogenic silica from RHs are mostly based on acidic pre-treatments for the removal of trace amounts of metals, followed by pyrolytic procedures carried out at variable temperatures and times usually in the range of 500-700 °C and 8-24 hours, respectively. 112 Conditions and process parameters (T and t) could be tailored to afford the synthesis of different added-value meso/macroporous silica. In this respect, one example described the pyrolysis of HCltreated RHs at 700 °C for 2 h for the preparation of amorphous silica nanoparticles with narrow size distribution of 25−30 nm (Figure 16, le ).…”
Section: Silica and Silicatesmentioning
confidence: 99%
“…NaOH (1-3 M) under both conventional or microwave-induced heating. 112,113 Under these conditions, the silica content of ash is dissolved forming sodium silicate which is then neutralized to precipitate silica gels (Scheme 2).…”
Section: Silica and Silicatesmentioning
confidence: 99%
“…Research shows that silica can be found in agriculture waste such as the rice husk ash and bamboo leaves ash respectively [7], [8]. The methods used to extract silica were via the acid leaching treatment such as the citric acid…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers such as K. G. Patel et al mentioned there are two ways of extracting silica by using thermal and chemical methods. The result showed using chemical method is more efficient and has extremely good quality [7]. Ghorbani et al, have successfully extracted 95.55% of high purity silica from the rice husk ash using 1 N of hydrochloric acid (HCI) followed by heat treatment of 600 °C [10].…”
Section: Introductionmentioning
confidence: 99%